Additional therapy improves outcomes in completely resected, limited-stage follicular lymphoma. Issue 13 (10th November 2019) - Andraos, Therese Y.; Ayoub, Zeina; Nastoupil, Loretta J; Milgrom, Sarah A.; Pinnix, Chelsea C.; Ng, Sweet Ping; Gunther, Jillian R.; Fowler, Nathan H.; Neelapu, Sattva S.; Samaniego, Felipe; Fayad, Luis E.; Dabaja, Bouthaina S.
Abstract: Patients with early-stage nodal follicular lymphoma (FL) may be rendered free of detectable disease by a diagnostic excisional biopsy. We reviewed the management and outcomes of 48 patients with FL, diagnosed from 2003–2013, treated at a single institution. The primary endpoints were local control (LC) and progression-free survival (PFS). Median age at diagnosis was 54.5 years (range 15–74 years). Forty-seven patients were stage I (97.9%); 15 patients (31.3%) had grade 3 disease. Initial management consisted of observation (12 patients; 25.0%), radiation therapy (RT) alone (12 patients; 25.0%), systemic therapy alone (9 cases; 18.8%), or both (15 patients; 31.3%). Median follow-up was 4.92 years (range 0.5–13.83 years). 4-year PFS and OS were 80.9% and 97.1%, respectively. Patients treated with additional therapy experienced significantly better 4-year LC (100% vs. 81.8%; p = .012) and 4-year PFS (86.7% vs. 63.6%; p = .006). Patients with completely resected limited-stage FL would benefit from therapy beyond excisional biopsy alone.